Extended Injection Intervals after Switching from Ranibizumab to Aflibercept in Macular Edema due to Central Retinal Vein Occlusion - Sylvia Nghiem-Buffet; Agnès Glacet-Bernard; Manar Addou-Regnard; Eric H. Souied; Salomon Y. Cohen; Audrey Giocanti-Auregan (Journal of Ophthalmology)
Purpose. To assess treatment interval extension after switching from ranibizumab to aflibercept intravitreal injections in macular edema (ME) due to central retinal vein occlusion (CRVO) with an insufficient response or frequent recurrences to initial treatment. Methods. CRVO eyes treated with ranibizumab injections on a treat-and-extend (TAE) basis with an insufficient response or frequent recurrences were switched to aflibercept. Primary endpoint was the change in injection intervals before and after the switch. Results. Eleven eyes were included in this retrospective bicentric study. Before switching, patients received a mean number of 15.3 ranibizumab injections (range, 6–34) during a mean follow-up of 23.4 months (range, 6–57). After switching to aflibercept, patients received a mean number of 12.4 injections (range, 6–20) during a mean follow-up of 25.5 months (range, 16–38). Treatment interval could be extended from 6.1 (range, 4–8) to 11 weeks (range, 8–16) (p=0.001) corresponding to a mean extension of injection interval of +4.9 weeks. Conclusion. In case of insufficient response or frequent recurrences of ME due to CRVO in patients treated with ranibizumab on a TAE basis, switching to aflibercept could allow extending treatment intervals, which could reduce the injection burden for these patients.